The presence of the past in French art, 1870-1905 modernity and continuity - Thomson, Richard 1953- (Yale University Press, 2021)
The study of late nineteenth- and early twentieth-century French art tends to focus on a search for the modern. Richard Thomson presents an innovative approach to a popular period of art history, instead investigating how art in early Third Republic France adapted styles from the past. The classical is the predominant theme, punctuated by other stylistic currents, notably the Rubensian and the Botticellian. It asks, how did these styles-all three derived from foreign art-come to be adapted into French visual culture? How did the Republic customise classicism to its ideological ends? How was classicism manipulated by progressive painters for radical and reactionary readings? The Presence of the Past in French Art 1870-1905 considers artists of very different character and type-from Degas to Henner, Cezanne to Besnard, Roty to Seurat, Dalou to Maillol-as well as a variety of media, including painting, sculpture, medals and celebrity photographs, to open up new vistas of interpretation in this fascinating field
Keywords: Geschichte 1870-1905; Kunst; Nationalbewusstsein; Kunststil; Frankreich